Students’ Cognitive and Attitude of Secondary School in Learning Global Warming using Student Team Achievement Division (STAD) based on Gender - Melvin Aldila; Fransisca Sudargo Tapilouw; Yayan Sanjaya (Journal of Science Learning, 2018)
This study was intended to investigate students’ cognitive and attitude of secondary school in learning global warming using Student Team Achievement Division (STAD) based on gender. This study was conducted at one of bilingual boarding school in Bandung. This study uses the quasi-experimental method with matching pretest-posttest comparison group design while the number of subject in the girl class is 15 (N=15) and in the boy class is 15 (N=15). Data was gained through a cognitive test which measured by Bloom's taxonomy cognitive level (C1-C6), a questionnaire which measured by Test of Science Related Attitude (TOSRA). The result shows that student who learns global warming using STAD has an improvement on their cognitive score, especially in the girl class. Meanwhile, girl class has higher students’ attitude result in three scales of TOSRA that are; attitude to scientific inquiry, adoption of a scientific attitude, and enjoyment of science lessons. Along with the students’ cognitive result, girl class also has a better science-related attitude than the boy class. Thus, it can be concluded that there is a significant difference between students’ cognitive and attitude at the girl and boy class in learning global warming using STAD.